Partial omission of bleomycin for early‐stage Hodgkin lymphoma patients treated with combined modality therapy: Does incomplete ABVD lead to inferior outcomes? - Jillian R. Gunther; Chelsea C. Pinnix; Gordon R. Glober; Kaitlin M. Christopherson; Penny Fang; Hun Ju Lee; Sairah Ahmed; Raphael E. Steiner; Ranjit Nair; Paolo Strati; Sattva S. Neelapu; Loretta J. Nastoupil; et al. (eJHaem, 2020)
Abstract Classical Hodgkin lymphoma (HL) patients achieve excellent outcomes; therefore, treatment de‐escalation strategies to spare toxicity have been prioritized. In a large randomized trial of early‐stage HL patients, omission of chemotherapeutic agents including bleomycin from the standard ABVD (doxorubicin, bleomycin, vinblastine, dacarbazine) regimen was not found to be noninferior; however, the effect of partial omission is unknown. We investigated the effect of bleomycin omission on outcome for 150 early‐stage HL patients. At 8 years, freedom from relapse was 99% for both patients who received complete or incomplete bleomycin, which is reassuring for patients requiring bleomycin omission due to toxicity.